Model Manajemen Wisata Halal Berkelanjutan: Analisis Literatur Konseptual dan Praktis - Laras Annisa Ulfitri Nedi (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
Halal tourism has emerged as a rapidly growing market segment within the global tourism industry. However, its development often focuses primarily on fulfilling the basic needs of Muslim travelers, without sufficiently addressing broader sustainability considerations. This article aims to analyze both conceptual and practical literature related to the sustainable management of halal tourism, identify research gaps, and propose a comprehensive management model. Through a systematic review of relevant scholarly articles, key dimensions of sustainability—economic, social, environmental, and spiritual—are identified as essential components to be integrated into halal tourism development. The proposed model emphasizes the importance of stakeholder collaboration, the application of technology, and the preservation of Islamic values in creating authentic and responsible tourism experiences. This article contributes to a deeper understanding of how halal tourism can be managed sustainably to generate long-term benefits for communities, the environment, and the tourism industry.